Trade and Transit Relations between Nepal and India: Political Implications - Timalsina, Saroj Kumar (The Journal of Economic Concerns, 2023)
The goal of this study is to learn more about the Nepal-India trade and transit situation, as well as to investigate the impact of trade and transit links on political relations. The descriptive and analytical data interpretation approaches employed to achieve the defined aims. According to the study's findings, Nepal-India trade and transit relations are critical because India has used Nepal's landlocked status and trade and transit dependency for political lobbying and has influenced Nepal's political and administrative sectors as a micromanager, which is not natural for any sovereign country. The paper examined the trade and transit scenario, as well as the issues that result from being on the outer edges of Indian entrenched interests in Nepali politics and administration.